КВАЗІДИНАМІЧНА МОДЕЛЬ ОЕС УКРАЇНИ ДЛЯ ДОСЛІДЖЕННЯ СТІЙКОСТІ ЗА ЧАСТОТОЮ - Павловський, В.В.; Лук’яненко, Л.М.; Стелюк, А.О.; Горошко, П.С. (Інститут електродинаміки Національної академії наук України, 2022)
Significant integration of renewables into Ukraine's interconnected power system (IPS) requires developing the appropriate quasi-dynamic (QD) model to study power system operation in such conditions. The work aims to create a QD model of the IPS of Ukraine considering renewables and consumption profiles of the Ukrainian IPS for the winter and summer character days. The corresponding approach to such a model development is presented in the paper. The load flow series simulation results based on the quasi-dynamic approach are also shown. Additionally, the frequency stability study results for the Ukrainian power system are depicted. Ref. 6, fig. 6.